(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
Integrated information about the distribution, coenotic affinity, ecological and morphological and biological peculiarities is listed in the Red Data Book of Ukraine of Astragalus ponticus. In modern area A. ponticus covers the steppe and forest-steppe regions of Circumboreal, Mediterranean, Iranian-Turanian regions. Characteristic traits of geographical distribution are revealed in each country. In Ukraine there are two centers of distribution of A. ponticus. The first is associated with steppe regions of the Dnieper upland and the Black Sea lowland. The second is located on the southern coast of the Crimea. It is given information about the ecological and coenotic affinity. In Ukraine populations of A. ponticus are local, numerically small, considered to be normally full, of generative individuals are dominated in the age range. The reasons for poor seed renewal of A. ponticus are identified. It is due to the poor seed productivity, controlled by pests seeds.